2020
DOI: 10.1155/2020/3656841
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiles Playing Opposite Roles of Pathogenesis in Schizophrenia and Glioma

Abstract: Background. Patients diagnosed with schizophrenia were found having lower risks to develop cancers, including glioma. Based on this epidemiology, we hypothesized that there were gene profiles playing opposite roles in pathogenesis of schizophrenia and glioma. Methods. Based on GEO datasets and TCGA, key genes of schizophrenia genes on the opposite development of glioma were screened by different expressed genes (DEGs) screening, weighted gene coexpression network analysis (WGCNA), disease-specific survival (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As for SLC12A6, its corresponding variant (rs117799466) increases the binding affinity for many TFs with repressive capabilities. The three TFs with the greatest binding affinity gains at this locus – SP1, ZN281, and MAZ – all play a role in neuronal differentiation 58,64,65 , and both SP1 and ZN281 have also shown increased expression levels in SCZ as well 66,67 . Combined with their increased binding affinity incurred by rs117799466, the upregulation of these TFs may contribute to the repression of SLC12A6, an outcome that has been previously linked to the potassium uptake impairments that characterize SCZ glia 53 .…”
Section: Introductionmentioning
confidence: 99%
“…As for SLC12A6, its corresponding variant (rs117799466) increases the binding affinity for many TFs with repressive capabilities. The three TFs with the greatest binding affinity gains at this locus – SP1, ZN281, and MAZ – all play a role in neuronal differentiation 58,64,65 , and both SP1 and ZN281 have also shown increased expression levels in SCZ as well 66,67 . Combined with their increased binding affinity incurred by rs117799466, the upregulation of these TFs may contribute to the repression of SLC12A6, an outcome that has been previously linked to the potassium uptake impairments that characterize SCZ glia 53 .…”
Section: Introductionmentioning
confidence: 99%
“…Through employment of bioinformatics tools like Weighted Gene Co-Expression Network Analysis (WGCNA) in several studies, interactions between risk co-expressed gene have been identi ed in patients with SCZ (20,21) in addition to normal and other mental diseases (22). For instance, Wen et al (23) identi ed 134 SCZ-speci c key genes using WGCNA and Radulescu et al (24) found 12 gene coexpression network modules in postmortem brain samples of SCZ patients. A number of other modules have been discovered using construction of WGCNA in other studies (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%